Migration and Acculturation: The Impact of Javanese Arrival in East Lombok on Education and Local Traditions - Yuliarstri, Widia; Eka Saputra, Bambang; Hafiz, Abdul; Murcahyanto, Hary (IJE : Interdisciplinary Journal of Education, 2024)
This study examines the impact of the arrival of Javanese communities in East Lombok on local education and traditions. The research employs a qualitative approach with data collection techniques including interviews and observations. Findings indicate that the migration of Javanese communities has brought significant changes in the social and cultural structure of East Lombok. In the context of education, their arrival has influenced the local education system both positively and negatively. Although there has been acculturation between Javanese and local cultures, some aspects of local traditions remain preserved. However, efforts are needed to maintain and develop education that reflects the original cultural identity of East Lombok while still accepting and appreciating cultural diversity.